Implementation of E-Government in Improving Public Service Efficiency: A Case Study on the Batu City Government - Hari Purnomo; Suljatmiko Suljatmiko; Ihsan Zikri Ulfiandi (Journal of Innovative and Creativity, 2025)
This study aims to analyze the implementation of e-Government in improving the efficiency of public services in the Batu City Government, especially through the Digital Public Service Mall (MPP) "Among Warga" service. Using a descriptive qualitative approach, data was obtained through interviews, observations, and documentation. The results show that service digitization is able to reduce the licensing process time from 3-5 days to 1-2 days, reduce administrative costs, and increase public satisfaction from 65% to 83%. However, obstacles were found in the form of limited digital human resources, lack of integration between OPDs, and low digital literacy of the community. This study aims to analyze the implementation of e-Government in improving the efficiency of public services in the Batu City Government, especially through the Digital Public Service Mall (MPP) "Among Warga" service. Using a descriptive qualitative approach, data was obtained through interviews, observations, and documentation. The results show that service digitization is able to reduce the licensing process time from 3-5 days to 1-2 days, reduce administrative costs, and increase public satisfaction from 65% to 83%. However, obstacles were found in the form of limited digital human resources, lack of integration between OPDs, and low digital literacy of the community.